Metabolic activity: A novel indicator of neuronal survival in the murine dopaminergic cell line CAD (2005)
Apoptosis is implicated in many neurodegenerative diseases, including Parkinson's disease (PD). Neuroprotective strategies targeting apoptosis need to preserve functional integrity of the saved cells to be effective. The aim of the present study was to evaluate a novel approach for analyzing neuronal function that monitors cellular metabolic responses to receptor activation using the microphysiometer. N-Acetyl-sphingosine (C2-ceramide) induced cell death of the neuronal cell line, Cath.a-differentiated (CAD) cells, which resemble catecholaminergic cells of the CNS, and provide a useful in vitro model for the cells affected in PD. C2-ceramide also suppressed the metabolic response of CAD cells to muscarinic receptor activation. Pretreatment with the caspase inhibitor Boc-Asp-(OMe)-fluoromethylketone (BAF) plusneurotrophin-3 (NT-3) reduced C2-ceramide-induced CAD cell death, delaying cell death more effectively than either agent alone; and, most significantly, BAF and NT-3 enabled the cells remaining 24 h after toxin treatment to generate a normal metabolic response to the muscarinic agonist carbachol. On the basis of these results, we suggest that measuring metabolic responses to receptor activation is a useful method for following neuronal viability after toxin treatment and that the combination of caspase inhibitors and neurotrophic factors might be a plausible strategy for improving neuronal survival, with critical preservation of metabolic function. Copyright © 2005 Humana Press Inc. All rights of any nature whatsoever reserved.